Designing training and instructional programs for older adults - Czaja, Sara J.; Sharit, Joseph (Human factors & aging series, 2013)
"Current and emerging trends in the domains of health management and the work sector, the abundance of new consumer products pervading the marketplace, and the desires of many older adults to undertake new learning experiences means that older adults, like their younger counterparts, will need to continually engage in new learning and training. Thus, understanding the challenges that older people face when confronted with new learning and training programs and developing potential strategies to overcome them is imperative. A comprehensive state-of-the-science review, Designing Training and Instructional Programs for Older Adults explores a broad range of issues, from the implications of theories of learning for designing instruction for older adults to adapting current perspectives on methods of instructional design to accommodate the capabilities and limitations of older learners. The authors provide an understanding of today's older adults, their demographics, their needs, the challenges facing them, and a realistic appraisal of their abilities and limitations's a basis for how current knowledge about training and instructional design should be shaped and applied to best accommodate this population of learners. They discuss topics such as retention and transfer of training, sequencing the order of instruction, e-learning, multimedia training formats, and the assessment and evaluation of training programs from the perspective of issues relevant to older learners. They also highlight the challenges presented by this very heterogeneous group that varies tremendously in backgrounds, skills, knowledge, and abilities.Focusing on how learning occurs, the authors' balanced coverage makes the book readable and enlightening across a wide spectrum of professionals and academics, including human factors/ergonomics specialists, gerontologists, managers, educators, undergraduate and graduate students, and the design community. The book supplies concise recommendations that will have direct impact on the design of instructional programs and for those individuals who are responsible for the training and performance of older people"--Provided by publisher.